Analisis Model Bisnis Wakaf Blockchain di Indonesia Menggunakan Model Bisnis Canvas - Firdaus, Artha Wirawan Yusuf (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
This article analyzes the blockchain waqf business model in Indonesia using the Business Model Canvas through literature review, expert interviews, and data analysis. The research findings indicate the potential for increasing waqf revenue. The practical implications serve as a guide for waqf developers and managers, as well as offering new insights to the public. This research represents an original contribution to understanding the blockchain waqf business model within the framework of the Business Model Canvas.